Isolated True Contractile Left Ventricular Diverticulum in an Adult Patient; A Case Report and Review of the Literature - Barutcu, Irfan; Gullu, Hakan; Yetkin, Ertan; Kosar, Feridun; Cehreli, Sengul (Annals of Medical Research, 2021)
None
Keywords: Isolated Ventricular Diverticulum, Chest Pain, Congenital Cardiac Malformation.